2021
DOI: 10.3390/s21217384
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Vibrotactile Belt on Emotionally Challenging Everyday Situations of the Blind

Abstract: Spatial orientation and navigation depend primarily on vision. Blind people lack this critical source of information. To facilitate wayfinding and to increase the feeling of safety for these people, the “feelSpace belt” was developed. The belt signals magnetic north as a fixed reference frame via vibrotactile stimulation. This study investigates the effect of the belt on typical orientation and navigation tasks and evaluates the emotional impact. Eleven blind subjects wore the belt daily for seven weeks. Befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similar techniques could be applied to sensory substitution, for instance, to compensate for sensory disability, disorder, or deficits [40,[118][119][120][121][122][123][124], or to other sensory augmentation devices to further enhance human perception by allowing humans to perceive information that they cannot naturally incorporate through their senses [27,[30][31][32][33][34][35]. Specifically, similar sensory augmentation techniques have been used to aid deaf and blind people during spatial navigation, showing that training with sensory augmentation devices can lead to improved navigational performance and reduced discomfort [46,121,125,126].…”
Section: Sensory Augmentation Can Enhance Human Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Similar techniques could be applied to sensory substitution, for instance, to compensate for sensory disability, disorder, or deficits [40,[118][119][120][121][122][123][124], or to other sensory augmentation devices to further enhance human perception by allowing humans to perceive information that they cannot naturally incorporate through their senses [27,[30][31][32][33][34][35]. Specifically, similar sensory augmentation techniques have been used to aid deaf and blind people during spatial navigation, showing that training with sensory augmentation devices can lead to improved navigational performance and reduced discomfort [46,121,125,126].…”
Section: Sensory Augmentation Can Enhance Human Performancementioning
confidence: 99%
“…A potential explanation is that the complex homing paradigm was conducted on a very small scale (19-22 m) [43] and could therefore have been solved by exclusively using the vestibular system [44,45]. Moreover, these studies were challenged with small sample sizes, for instance, due to time-intensive experimental procedures [41,43] or a focus on specific test subjects [40,46]. Interestingly, previous research investigating spatial knowledge in real-world environments identified the challenge that there is a large interindividual variability in spatial navigation ability and the acquisition of spatial knowledge across the population [47][48][49], which increases even more when factors such as the degree of familiarity with the environment are likely to impact the results.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite rapid advancements, a significant barrier to long-term adoption exists: a large percentage of users discontinue the use of these wearables over time. For instance, as many as 40% of individuals fitted with a prosthesis either rarely use it or abandon it altogether (Biddiss and Chau, 2007;Brandebusemeyer et al, 2021). Preliminary evidence suggests that one key reason for this attrition is the increased cognitive load and explicit device awareness imposed by these devices (Slater et al, 2003;Murray, 2004;Li et al, 2019;Danry et al, 2022) such as increased attention, concentrates or focalization of the devices in our immediate experience (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation is that the complex homing paradigm was conducted on a very small scale (1922 meters; 44) and could therefore have been solved by exclusively using the vestibular system (45, 46). Moreover, these studies were challenged with small sample sizes, for instance, due to time-intensive experimental procedures (42, 44) or a focus on specific test subjects (i.e., 41,47). Interestingly, previous research investigating spatial knowledge in real-world environments identified the challenge that there is a large interindividual variability in spatial navigation ability and the acquisition of spatial knowledge across the population (4850) which is increased even more when factors such as the degree of familiarity with the environment are likely to impact the results.…”
Section: Introductionmentioning
confidence: 99%